German translation, cultural adaption and validation of the unidimensional self-efficacy scale for multiple sclerosis: a study protocol. Issue 8 (20th August 2019) - Seebacher, Barbara; Mills, Roger J; Reindl, Markus; Zamarian, Laura; Kuisma, Raija; Kircher, Simone; Brenneis, Christian; Ehling, Rainer; Deisenhammer, Florian
Abstract : Introduction: Self-efficacy refers to individuals' confidence in their ability to perform relevant tasks to accomplish desired goals. This is independent of their actual abilities. In people with multiple sclerosis (MS), self-efficacy has been shown to powerfully influence motivation and health-related behaviour, such as adherence to prescribed treatment or physical activity. So far, a rigorously tested German language self-efficacy questionnaire for people with MS is missing. Methods: The purpose of this study is to translate the original Unidimensional Self-Efficacy Scale for Multiple Sclerosis (USE-MS) into German and to validate the German USE-MS (USE-MS-G). Based on Bandura's concept of self-efficacy and international guidelines for questionnaire development, the patient-led development of the pre-final German version will involve a forward–backward translation process, synthesis of translations, expert committee review and consensus with the original test developers. At two centres in Tyrol, Austria, content and face validity and cultural adaption for Austria will be established using face-to-face semistructured cognitive interviews of 30 people with MS (PwMS). A further 292 PwMS with minimal to severe disability will be tested at two timepoints to validate the USE-MS-G. Results: Mixed methods analyses will be applied. Interviews will be transcribed and analysed employing qualitative content analysis. External validity will be explored using Spearman's Rank correlation coefficients of the USE-MS-G with the 13-item Resilience Scale, General Self-Efficacy Scale, Multiple Sclerosis International Quality of Life questionnaire, Hospital Anxiety and Depression Scale and MS-specific Neurological Fatigue Index. Test–retest reliability, internal consistency and floor and ceiling effects will be evaluated. Internal validity will be examined using Rasch analysis. Ethics and dissemination: Ethical approval was received from the Ethics Committee of the Medical University of Innsbruck, Austria (reference number EK1260/2018; 13.12.2018). Results from this study will be disseminated to the participants and MS Societies, and to clinicians and researchers through peer-reviewed publications and conferences. Study registration: ISRCTN Registry; trial ID ISRCTN14843579 ; prospectively registered on 02. 01. 2019; http://www.isrctn.com/ISRCTN14843579